Two-Dimensional Lattice-Gas model for methane clathrate Hydrates: Comparative analysis with experiments and Three-Dimensional simulations - Juan, Julián (2025)
Methane clathrate hydrates, particularly those with an sI structure, are significant due to their potential as energy resources and their impact on gas pipelines. In this study, a two-dimensional (2D) lattice-gas model is employed to investigate the main thermodynamic properties of methane clathrate hydrates. The proposed framework is validated through comparison with experimental data and more advanced three-dimensional (3D) simulations. Adsorption isotherms, dissociation enthalpy and phase stability of the sI structure are evaluated using Monte Carlo (MC) simulations in the grand canonical ensemble. The 2D adsorption isotherms demonstrate a strong alignment with both experimental data and 3D simulations, thereby highlighting the 2D model’s ability to accurately represent both rigid and flexible sI structures. The dissociation enthalpy calculated using the proposed approach (76.4 kJ/mol) excellently matches the experimental value (78 kJ/mol), thus confirming the model’s validity. Furthermore, the phase diagram calculated using the Clausius-Clapeyron equation shows very good agreement with experimental data between 260 and 290 K, with deviations observed above this temperature. These findings highlight the efficacy and robustness of the 2D model in studying methane clathrate hydrates and suggest its potential applicability for investigating other guest species and hydrate structures.